Pengaruh Pemberian Ekstrak Umbi Bawang Dayak (Eleutherine palmifolia L. Merr.) Terhadap Kadar Mda (Malondialdehid) Serum Tikus Putih (Rattus norvegicus) Jantan Galur Wistar Yang Diinduksi Parasetamol - William Sugiharto; Tri Martini (Universitas Hang Tuah, 2018)
ABSTRACT Background: Paracetamol induced hepatotoxic effect because paracetamol increased production of N-acetyl-para-benzoquinone imine (NAPQI). Dayak onion contains flavonoids that inhibits cytochrome P450 activity, increases Glutation S-transferase (GST) activity, and scavenges free radicals. Method: This study used 24 male wistar rats (Rattus norvegicus) divided into 3 groups: group of rats without paracetamol induction, group of rats induced by 1750mg/kgBW paracetamol on 14th day, and group of rats given 300mg/kgBW dayak onion bulb extract (Eleutherine palmifolia L. Merr) for 14 days and induced by 1750 mg/kgBW paracetamol on 14th day. Result: The result of One Way Anova showed that serum malondialdehyde level of group of rats induced by paracetamol ( =129,063±42,0497mg/dl) was significantly higher (p=0.006) than group of rats without paracetamol induction ( =85,688±15,9976mg/dl). Serum malondialdehyde (MDA) level of group of rats given dayak onion bulb extract induced by paracetamol ( =118,500±19,4054mg/dl) was not significantly lower (p=0,463) than group of rats induced by paracetamol ( =129,063±42,0497mg/dl). Conclusion: The conclusion of this study showed that paracetamol significantly increased serum malondialdehyde (MDA) level and dayak onion bulb extract was not significantly decreased serum malondialdehyde (MDA) level.